Relationship Between Selected Rice Plant Landraces, Bacteria and Yellow Stemborer from Sarawak - Yin Hui, Cheok (Universiti Malaysia Sarawak, 2022)
Yellow stemborer (YSB) (Lepidoptera: Crambidae: Scirpophaga incertulas) is a monophagous insect pest that threatening the production of rice, a human staple food plant. It is speculated that the bacterial community associated with both rice plants and YSB are involved in the feeding process of YSB on rice plants. Sarawak has a wide variety of local rice landraces, which may harbour special bacteria communities that contribute to YSB resistance. There is a need to profile the bacterial community associated with local rice landraces and YSB. However, there is a lack of bacterial profiling for Sarawak local rice landraces as well as YSB. Therefore, 16S rDNA amplicon sequencing technique was used to characterise the bacterial community associated with YSB larvae and three selected Sarawak local rice landraces viz. Bajong, Bario, and Bubok. On top of that, the bacterial diversity and composition were compared between bacterial communities from three rice landraces and two rice plant organs. The involvement of YSB infestation in the changes in bacterial community in rice plants was understudied. Therefore, this study also aimed to investigate the change in the diversity and composition of bacterial communities by comparing the bacterial community from YSB free and YSB infested samples. The bacterial community of both YSB and rice plants was dominated by bacteria from phylum Proteobacteria. There is no significant difference in the bacterial diversity of bacterial community associated with three rice landraces, nor do they differ in terms of bacterial composition. Determination of bacterial diversity by rice plant organs was only shown by Faith’s phylogenetic diversity, where the leaf blade has a phylogenetically more diverse bacterial community than the rice stem. The bacterial composition of rice plants was predominantly determined by rice plant organs. YSB infestation had a significant effect on the rice plant's bacterial diversity and composition. Generally, bacterial diversity in rice plants decreased posterior to YSB infestation. The bacterial genera shared between YSB and rice plants infested by YSB but absent in YSB free rice plants suggested a possible bacterial transmission from YSB to rice plants. This result may suggest that YSB infestation has affected the bacterial community of rice plants.